OPTIMALISASI PEMBENTUKAN KARAKTER DISIPLIN MELALUI PEMBIASAAN BARIS BERBARIS PESERTA DIDIK KELAS 4 SDN PENGKOL 01 - Farida Nugrahani; Ahza Fatekhah Choirun Nisa; Andres Alam Dewangga; Dahestin Yusehadi; Elfira Amalia Hakiki; Hana Zakiyyah; Kiki Dwi Fani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education now aims not only to improve academic knowledge but also to foster character development, particularly in addressing moral and mental decline among students. Primary schools play an important role in instilling core values through character education programs and daily habits. An important habit that needs to be cultivated is discipline, which is formed through habitual reinforcement of behavior. Discipline is an important activity that involves guidance from adults to support children's growth as social beings. Schools serve as an important environment for character education, requiring cooperation between teachers, school leaders and parents. The implementation of the pre-class marching routine aims to foster discipline, responsibility and respect among Grade 4 students of SDN Pengkol 01. However, observations revealed various challenges, including student indifference and lack of discipline. A qualitative narrative approach was used to investigate the role of teachers in discipline formation through the marching routine, utilizing interviews and participatory observation. Analysis showed that although there were positive developments in student discipline, such as improved punctuality and cohesiveness, inconsistencies were still prevalent. Teacher engagement is crucial for effective implementation, and innovations in routine activities can increase engagement.